Synthesis and characterization of partially bio-based polyimides based on biphenylene-containing diisocyanate derived from vanillic acid - Kuhire, Sachin S.; Ichake, Amol B.; Grau, Etienne; Cramail, Henri; Wadgaonkar, Prakash P. (European Polymer JOurnal, 2018)
A new bio-based biphenylene-containing diisocyanate, namely, 5,5'-diisocyanato-2,2',3,3'-tetramethoxy-1,1'-biphenyl (BDI) was synthesized starting from vanillic acid - a lignin-derived phenolic acid. A series of new partially bio-based polyimides was prepared by polycondensation of BDI with five commercially available aromatic dianhydrides. Polyimides exhibited good solubility in organic solvents and medium molecular weights (Mn (GPC, polystyrene standard) = 25,100-32,200 g mol(-1)). Polyimides showed good thermal stability with 10% degradation temperature and glass transition temperature in the range 459-473 degrees C and 262-329 degrees C, respectively.